The Principles and the Method of Vipassana Meditation - Dhakhwa, Shanta Bahadur (Journal of Population and Development, 2022)
The current article is a scientific research of the method of Vipassana Meditation which was discovered by the Buddha. The paper briefly outlines the fundamental principles involved in the meditation practice regarding the concept of Anicca, Dukkha and Anatta. It briefly outlines method of Vipassana meditation step by step at it is practiced. More focus is given in revealing the practical methodology of the Meditation. Primary Buddhist texts of Tipitaka are taken for reference.